2018
DOI: 10.1093/brain/awy154
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament as a predictor of disease worsening and brain and spinal cord atrophy in multiple sclerosis

Abstract: Neuro-axonal injury is a key factor in the development of permanent disability in multiple sclerosis. Neurofilament light chain in peripheral blood has recently emerged as a biofluid marker reflecting neuro-axonal damage in this disease. We aimed at comparing serum neurofilament light chain levels in multiple sclerosis and healthy controls, to determine their association with measures of disease activity and their ability to predict future clinical worsening as well as brain and spinal cord volume loss. Neurof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

41
449
8
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 405 publications
(504 citation statements)
references
References 25 publications
41
449
8
6
Order By: Relevance
“…Additionally, 30 age‐matched healthy controls were included, and age‐adjusted reference values of a large cohort investigated earlier by our laboratory were used …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 30 age‐matched healthy controls were included, and age‐adjusted reference values of a large cohort investigated earlier by our laboratory were used …”
Section: Methodsmentioning
confidence: 99%
“…16 The concentration of NFL is elevated in the cerebrospinal fluid (CSF) of MS patients, 17 and it is reduced by effective immunomodulatory treatments such as fingolimod and natalizumab. 22,23 Only one observational study has so far addressed the relationship between vitamin D and NFL in MS, showing that high serum levels of 25-hydroxyvitamin D were associated with low CSF levels of NFL. 22,23 Only one observational study has so far addressed the relationship between vitamin D and NFL in MS, showing that high serum levels of 25-hydroxyvitamin D were associated with low CSF levels of NFL.…”
mentioning
confidence: 99%
“…Most notably, higher serum NfL levels were further related to future brain and cervical spinal volume loss in this study. 7 These are very promising results that support the potential clinical value of Nf measurements in MS. In particular, serum NfL chain levels can be regarded as an easy-to-measure marker of neuro-axonal damage in MS.…”
mentioning
confidence: 66%
“…6 Several studies have proven that NfL in CSF and serum are very well correlated to each other, supporting the notion that serum NfL may be used as a bloodderived marker for neuro-axonal damage. [7][8][9] There is evidence showing that both CSF and serum Nfs levels are associated with disease activity, physical disability, and magnetic resonance imaging (MRI) changes in MS; however, clinical follow-up time was relatively short in most of these studies. 1,2,7 In a recent study in 51 MS patients, it has been shown that higher CSF NfH values could prognosticate an unfavourable disease evolution during a follow-up time of 15 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation